The role of risk in the context of climate change, land use choices and crop production: Evidence from Zambia - De Pinto, Alessandro; Smith, Vincent H.; Robertson, Richard D. (Inter-Research Science Publisher, 2019)
Most of the studies that investigate the impacts of climate change on agriculture have concentrated on the effects of changes in mean temperature and precipitation even though the importance of volatility and risk on farmers’ decision making is well documented. This study examines the empirical importance of the effects of risk associated with the impacts of climate change on farm land allocations and consequent effects on agricultural output in Zambia. We used a discrete-choice model consistent with a mean-variance utility function to model farm-level land allocations among alternative crops. Results indicate that risk-reducing decisions can reinforce crop shifts driven by climate change impacts on mean temperature and precipitation. While an analysis of the available per-capita daily nutrients reveals that farmers’ crop allocation choices can mitigate the negative effects of climate change, the opportunity cost of these decisions is explored through a simulation scenario in which yield variability is reduced to zero. Reduction of yield variability leads to land allocations that result in a sizable increase in total crop production and a significant increase in available per capita daily calories. Important conclusions can be derived from this analysis. First, the risk environment matters and should not be ignored. When the economic effects of climate change are considered, decision making under uncertainty and risk should be at the forefront of the problems that need to be addressed. Second, concentrating on farm-level effects of responses to climate change is not sufficient. To understand the economy-wide consequences of climate change, the aggregate effects of individual decisions should be assessed. Third, results indicate that increased efforts in risk management and in developing policies aimed at reducing risk can lead to significant positive outcomes for the nutritional status of low-income, food-insecure populations.